Topochemical reduction of the Ruddlesden-Popper phases Sr2Fe(0.5)Ru(0.5)O4 and Sr3(Fe(0.5)Ru(0.5))2O7. - Denis Romero, F; Gianolio, D; Cibin, G; Bingham, P; d'Hollander, J; Forder, S; Hayward, M (2013)
Reaction of the Ruddlesden-Popper phases Sr2Fe(0.5)Ru(0.5)O4 and Sr3(Fe(0.5)Ru(0.5))2O7 with CaH2 results in the topochemical deintercalation of oxide ions from these materials and the formation of samples with average compositions of Sr2Fe(0.5)Ru(0.5)O(3.35) and Sr3(Fe(0.5)Ru(0.5))2O(5.68), respectively. Diffraction data reveal that both the n = 1 and n = 2 samples consist of two-phase mixtures of reduced phases with subtly different oxygen contents. The separation of samples into two phases upon reduction is discussed on the basis of a short-range inhomogeneous distribution of iron and ruthenium in the starting materials. X-ray absorption data and Mössbauer spectra reveal the reduced samples contain an Fe(3+) and Ru(2+/3+) oxidation state combination, which is unexpected considering the Fe(3+)/Fe(2+) and Ru(3+)/Ru(2+) redox potentials, suggesting that the local coordination geometry of the transition metal sites helps to stabilize the Ru(2+) centers. Fitted Mössbauer spectra of both the n = 1 and n = 2 samples are consistent with the presence of Fe(3+) cations in square planar coordination sites. Magnetization data of both materials are consistent with spin glass-like behavior.